Transplantation of a beating heart: A first in man - Shengli Yin; Jian Rong; Yinghua Chen; Lu Cao; Yunqi Liu; Shaoyan Mo; Hanzhao Li; Nan Jiang; Han Shi; Tielong Wang; Yongxu Shi; Yanling Zhu; et al. (Elsevier, 2022)
Summary: Background: In the current practice, graft ischaemia and reperfusion injury (IRI) is considered an inevitable component in organ transplantation, contributes to compromised organ quality, inferior graft survival and limitations in organ availability. Among all the donor organs, the heart is most vulnerable to IRI and the tolerated ischaemic time is the shortest. Methods: By combining adapted surgical techniques and normothermic machine perfusion (NMP), we performed the first case of ischaemia-free beating heart transplantation (IFBHT) in man. The donor heart was procured after an in situ NMP circuit was established, then underwent ex situ NMP and implanted under NMP support. The post-transplant graft function was monitored. Findings: The donor heart was procured, preserved, and implanted under a continuously perfused, normothermic, oxygenated, beating state. During ex situ NMP, the donor heart beat with sinus rhythm and adequate ventricular contraction, consumed oxygen and lactate, suggesting a good cardiac function. The dynamic electrocardiogram demonstrated an absence of ischaemic injury of the donor heart during the entire procedure. The echocardiogram showed an immediate graft function with a left ventricle ejection fraction (LVEF) of 70%. The patient was discharged on post-transplantation day 20 and was followed up for 8 months with normal cardiac function and life. Interpretation: This study shows the feasibility of IFBHT procedure, which might be able to completely avoid graft IRI, has thus the potential to improve transplant outcome while increasing organ utilization. Funding: This study was funded by National Natural Science Foundation of China, Guangdong Provincial Key Laboratory Construction Projection on Organ Donation and Transplant Immunology, and Guangdong Provincial International Cooperation Base of Science and Technology.